2018
DOI: 10.1155/2018/2420809
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effects of Gagam‐Sipjeondaebo‐Tang, a Novel Herbal Formula, against MPTP‐Induced Parkinsonian Mice and MPP+‐Induced Cell Death in SH‐SY5Y Cells

Abstract: Parkinson's disease is a neurodegenerative disease characterized by progressive cell death of dopaminergic neuron and following neurological disorders. Gagam-Sipjeondaebo-Tang (GST) is a novel herbal formula made of twelve medicinal herbs derived from Sipjeondaebo-Tang, which has been broadly used in a traditional herbal medicine. In the present study, we investigated the effects of GST against 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-induced motor abnormalities in mice and 1-methyl-4-phenylpyridini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…More number of dopaminergic neurons and apoptosis was seen in the substantia niagra region in the MPTP group, and treatment with HPE reduced the toxicity of MPTP in brain tissue (Ko et al, 2018). All these indings support that HPE offers neuroprotection against MPTP-induced Parkinson's disease model.…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…More number of dopaminergic neurons and apoptosis was seen in the substantia niagra region in the MPTP group, and treatment with HPE reduced the toxicity of MPTP in brain tissue (Ko et al, 2018). All these indings support that HPE offers neuroprotection against MPTP-induced Parkinson's disease model.…”
Section: Resultssupporting
confidence: 54%
“…The fresh brain was serially sectioned and the striatum was separated. The tissue was homogenised in an ice-cold solution of 0.1% M PBS and used for further analysis (Ko et al, 2018).…”
Section: Experimental Groupingmentioning
confidence: 99%
“…In recent years, other herbal extract have also been studied for their neuroprotective effects. Gagam-Sipjeondaebo-Tang (100 μg/ml) could reverse cell viability inhibited by 1 mM MPTP, which was a little weaker compared with the effect of the CT extract here (Ko et al, 2018). Therefore, we suggested that the CT extract might be a candidate for the treatment and prevention of neurodegenerative disease.…”
Section: Discussionmentioning
confidence: 75%
“…SDT was also found to reduce inflammation in a mouse model of muscle atrophy by reducing inflammatory cytokines [17]. In previous studies, GST inhibited neuronal death activation in a PD mouse model [18], but the effect of GST on inflammation has not been well studied. Moreover, co-administration of GST with conventional drugs has not been well studied.…”
Section: Introductionmentioning
confidence: 94%
“…Experiment groups are as following; control group (administration of saline for 5 day), MPTP group (administration of saline for 5 day, MPTP 20 mg/kg intraperitoneal injections 4 times at 2 h interval), MPTP + GST group (administration of GST 200 mg/kg for 5 day), MPTP + ibuprofen group (administration of ibuprofen 80 mg/kg for 5 day) and MPTP + GST + ibuprofen group (administration of GST 200 mg/kg and ibuprofen 80 mg/kg for 5 day). The dose of all treatments was followed by our previous study [18].…”
Section: Animals and Experiments Designmentioning
confidence: 99%